Achieving development success: Strategies and lessons from the developing world - Augustin Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper provides a synthesis of successful strategies and implied lessons for development success, employing at least six themes on in-depth case studies of a large number of developing countries around the world. The coverage includes East Asia and the Pacific (South Korea, Malaysia, Thailand, and Vietnam), the Emerging Asian Giants (China and India), Sub-Saharan Africa (Botswana, Ghana, Mauritius, and South Africa), Latin America and the Caribbean (Brazil, Chile, Costa Rica, and the Dominican Republic), and the Middle East and North Africa (Bahrain, Oman, Tunisia, and the United Arab Emirates), along with the respective regional syntheses. Although countries' experiences are not necessarily replicable, the recurrent themes across countries and regions provide the appropriate connectedness for fostering a truly global perspective on development strategies and lessons from the developing world.
Keywords: N10; O50; P52; 330; development success; strategies and lessons; developing world; Entwicklungsstrategie; Entwicklungsländer